Distinctive Attitude of Datuk Maringgih in Marah Rusli’s Novel Siti Nurbaya - Rizkya, Rahmi; Manugeren, M.; Ekalestari, Susi (KnE Social Sciences, 2019)
This research deals with the distinctive attitude of Datuk Maringgih in Marah Rusli’s novel Siti Nurbaya. Datuk Maringgih is described as a person who is old, strong, rebellious and has a lot of money and always has a strategy in everything. The attitude shown by this person is also related to society. The research is conducted means of descriptive qualitative method. Qualitative research is a research method that focuses on understanding social phenomena that occur in society. Descriptive qualitative is usually designed to examine morality and other problems in society. The researcher uses attitude theory where attitude is a mental and neural state of readiness, organized through experience, exerting a directive or dynamic influence on the individual’s response to all objects and situations with which it is related. The source of data is from the novel. The data in this research is the entire texts in the book. The technique used to analyze data is heuristic and hermeneutic. The research result shows that Datuk Maringgih had three distinctive attitudes: Defending land from the invaders, helping others and consistence. Keywords: Consistency, land defense, attitude.